New technologies - a source of inspiration and a tool for interactive and immersive experiences - Benescu, Vlad (Journal of Danubian Studies and Research, 2023)
New technologies are influencing the sphere of performing arts with new possibilities for storytelling and the possibility of building a different kind of bridge between artistic creation and spectators. The objective of this article is to demonstrate how a context involving new technologies can facilitate an interactive and immersive environment in which the spectator can easily venture without feeling that his involvement in the artistic product implies an uncomfortable activity. In this article I will use as a case study a performing arts research project conducted in the summer of 2022 entitled Transsystemic Signals 2.0. This project brought together theatre artists and digital arts artists and aimed to explore the innovative-creative potential of the tools offered by new media. To analyse this research project I will first define what constitutes the interactive and immersive nature of an artistic product. During the course of my scientific research I have participated in several projects that integrated new technologies and I have fulfilled several functions: actor, dancer, director, choreographer, technician, cameraman, lighting technician, digital artist, which helped me to have an objective vision of the phenomenon.